Paracrine effects of embryo-derived FGF4 and BMP4 during pig trophoblast elongation - Valdez Magana, Griselda; Rodríguez, Aida; Zhang, Haixin; Webb, Robert; Alberio, Ramiro (Elsevier, 2014)
The crosstalk between the epiblast and the trophoblast is critical in supporting the early stages of conceptus development. FGF4 and BMP4 are inductive signals that participate in the communication between the epiblast and the extraembryonic ectoderm (ExE) of the developing mouse embryo. Importantly, however, it is unknown whether a similar crosstalk operates in species that lack a discernible ExE and develop a mammotypical embryonic disc (ED). Here we investigated the crosstalk between the epiblast and the trophectoderm (TE) during pig embryo elongation. FGF4 ligand and FGFR2 were detected primarily on the plasma membrane of TE cells of peri-elongation embryos. The binding of this growth factor to its receptor triggered a signal transduction response evidenced by an increase in phosphorylated MAPK/ERK. Particular enrichment was detected in the periphery of the ED in early ovoid embryos, indicating that active FGF signalling was operating during this stage. Gene expression analysis shows that CDX2 and ELF5, two genes expressed in the mouse ExE, are only co-expressed in the Rauber's layer, but not in the pig mural TE. Interestingly, these genes were detected in the nascent mesoderm of early gastrulating embryos. Analysis of BMP4 expression by in situ hybridisation shows that this growth factor is produced by nascent mesoderm cells. A functional test in differentiating epiblast shows that CDX2 and ELF5 are activated in response to BMP4. Furthermore, the effects of BMP4 were also demonstrated in the neighbouring TE cells, as demonstrated by an increase in phosphorylated SMAD1/5/8. These results show that BMP4 produced in the extraembryonic mesoderm is directly influencing the SMAD response in the TE of elongating embryos. These results demonstrate that paracrine signals from the embryo, represented by FGF4 and BMP4, induce a response in the TE prior to the extensive elongation. The study also confirms that expression of CDX2 and ELF5 is not conserved in the mural TE, indicating that although the signals that coordinate conceptus growth are similar between rodents and pigs, the gene regulatory network of the trophoblast lineage is not conserved in these species.